2010
DOI: 10.1007/s00508-010-1384-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute gouty arthritis in a patient after total knee arthroplasty

Abstract: Symptomatic gout in an artificial joint is exceptionally rare. We present a 68-year-old male patient who developed progressive knee pain and swelling one year after the cemented total arthroplasty of his left knee. The diagnosis was confirmed by crystal identification in the synovial fluid. Beside thorough workout to rule out infection in a painful and inflamed prosthetic knee, specific history of gout should be sought and fluid aspirate examined cytologically and under polarised light for crystal arthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Joint movements were universally restricted on admission across the studies reviewed, and this was more pronounced amongst pseudogout patients with a mean reported range of motion of 57°, see table 3. [12] P Blyth & V S Pai [13] M J Archibeck et al [14] G Roberts [15] L Crawford et al [16] J C Rompen et al [17] J W Salin et al [18] J S Berger et al [19] S K Fokter et al [20] M T Freehill et al [21] A Zadaka et al [22] S Soloway [23] [25] G Holt et al [26] C Hirose & R Wright [27] P Sonsale et al [28] J L Carter et al [29] T Hunte et al [30] K Koyama et al [31] G Levi et al [32] K Harato& H Yoshida [33] Article Type Case Series ( …”
Section: Presenting Features and Clinical Examinationmentioning
confidence: 99%
“…Joint movements were universally restricted on admission across the studies reviewed, and this was more pronounced amongst pseudogout patients with a mean reported range of motion of 57°, see table 3. [12] P Blyth & V S Pai [13] M J Archibeck et al [14] G Roberts [15] L Crawford et al [16] J C Rompen et al [17] J W Salin et al [18] J S Berger et al [19] S K Fokter et al [20] M T Freehill et al [21] A Zadaka et al [22] S Soloway [23] [25] G Holt et al [26] C Hirose & R Wright [27] P Sonsale et al [28] J L Carter et al [29] T Hunte et al [30] K Koyama et al [31] G Levi et al [32] K Harato& H Yoshida [33] Article Type Case Series ( …”
Section: Presenting Features and Clinical Examinationmentioning
confidence: 99%
“…There have been limited case reports in the literature of patients with simultaneous gout flares and infection, [ [3] , [4] , [5] ] but there have only been 10 reported cases of aseptic gout flare after TKA [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. In these previous reports, all without alpha-defensin testing, most patients underwent debridement and implant retention (DAIR) and were treated postoperatively with a combination of nonsteroidal anti-inflammatories or allopurinol [ [5] , [6] , [7] , [8] ].…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic gouty arthropathy has been shown to resemble PJI in previous literature [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Periprosthetic gout can therefore be difficult to distinguish from infection for a multitude of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…В ряде случаев наличие сопутствующей патологии может значительно затруднить диагностику проблемы. например, в литературе описаны редкие случаи острого воспаления прооперированного коленного сустава на фоне обострения подагры [39][40][41]. В ходе исследования мы столкнулись с тремя подобными случаями, в связи с чем было принято решение о необходимости определения уровня мочевой кислоты в крови и, при необходимости, проведения исследования синовиальной жидкости на наличие кристаллов.…”
Section: Discussionunclassified